PEMAKNAAN PENONTON PADA FILM DOKUMENTER “THE SOCIAL DILEMMA” - Rugayah, Rugayah; Noor Rakhmad, wiwid; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
"”The social Dilemma" is a film that discusses the other side of social media. Social media, which plays a big role in community's lives now, also has the same big consequences, but the behavior of people using social media has not change. This research aims to find out how the audience as social media users interpret the message or meaning in the documentary film "”The Social Dilemma" using descriptive qualitative research methods through the Reception Analysis approach and The Code of Television Theory. The results of the research after going through the analysis process using the Reception Analysis theory approach which consists of 3 (three) positions show that all the informants consisting of 5 (five) informants as viewers are in a position of Hegemony when interpreting the message or meaning that contained in the documentary film "The Social Dilemma” which is at 3 (three) levels that have been found in accordance with the theoretical approach of The Code of Television. There were no informants who were in a Negotiation or Opposition position. Based on these results, it can be concluded that there are similarities in meaning between what the informants mean and the message or meaning conveyed in the documentary film "The Social Dilemma" regarding the use of a social media.